Attract Tiles Supplier Sdn. Bhd / Hairul Lisa Hj Abd Latif ... [et al.] - Hj Abd Latif, Hairul Lisa; Zainudin, Zailiana; Arbain, Rosilah; Ruslin, Rosliza (2002)
Attract Marble Supplier is to ensure that we will achieve organization target. Each member of Attract Marble Supplier should be counted to transform the company to the highest capability.